Abstracts Communications Orales –Musculo-squelettiques_ JRANF 2025_JAIM 2025_17.3 - MOULION TAPOUH Jean Roger; MOIFO Boniface; DIARRA LASSENI; OKIEMY NIENDET CP; AKPO G; Hamidou DEME; TAMBALA Chris Borel; GANIOU TIDJANI KABIROU; F. ELILIE MAWA ONGOTH; TSOU MISSIE LE; et al. (Journal Africain d Imagerie Médicale (J Afr Imag Méd) Journal Officiel de la Société de Radiologie d’Afrique Noire Francophone (SRANF), 2025)
6- Abstracts Communications Orales –Musculo-squelettiques_ JRANF 2025_JAIM 2025_17.3